Evaluating the shifts in the South African cotton industry: The effects of institutional transformation and international cotton price dynamics - Davids, Patricia (Tracey) (University of Pretoria, 2022)
Dissertation (MSc (Agric) Agricultural Economics)--University of Pretoria, 2022.